THE EFFECTIVENESS OF A NEW FOOD SUBSTANCE - A HARD GELATIN CAPSULE - «VIZION JUNIOR» IS BEING STUDIED IN CHILDREN WHO HAVE RECOVERED FROM THE CORONAVIRUS. (World Bulletin of Public Health, 2023)
Based on the results of our own research, a new food product has been developed - prophylactic capsules - «Vizion Junior» produced, contains a sufficient amount of protein, minerals, vitamins and dietary fiber. The study of effectiveness in patients with coronavirus showed: normalization of metabolism; improvement of hematological parameters, decrease in plasma concentration of liver enzymes (AST, ALT and GGT), as well as total bilirubin, which characterize the detoxification activity of the liver.